A Comparative Study of KWL and TWA Techniques upon Studentsâ Reading Competency at SMAN 1 Singaraja - Ekayani, Ni Wayan (Universitas Pendidikan Ganesha, 2017)
This research aimed at testing which technique between KWL and TWA techniques is better to be used in order to help students in promoting their reading competency to achieve the performance indicator which is set to the tenth-grade students at SMAN 1 Singaraja. The design of the study was Post-test Only Two Non-Control Group Design. The population was 11 classes with 317 tenth-grade students at SMAN 1 Singaraja in which 2 classes were selected as the sample of the research which was determined by using cluster random sampling. One class with 28 students read texts using KWL and the other class with 30 students read texts using TWA technique. The instruments which were used such as lesson plans, try out test and final test. The data were collected through reading test (final test) that were analysed descriptively and inferentially which used one-way ANOVA in inferential statistics analysis. The result shows that, F=1.863 with the significance value was 0. 140 which was higher than the significance value of alpha, 0.05. Thus, there is no significant difference on the studentsâ reading competency when they read texts using KWL and TWA technique. Because there is no different on the studentsâ reading competency between the two groups when they read texts using KWL and TWA techniques, Turkey analysis did not need to be administrated.